2017
DOI: 10.3892/etm.2017.4396
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of NF-κB in viral encephalitis of children

Abstract: The aim of this study was to analyze the concentration changes of nuclear factor-κB (NF-κB) and the related inflammatory factors of pre-treatment and post-treatment in children with viral encephalitis, to examine the mechanism of NF-κB in the pathogenesis of child viral encephalitis. Twenty-two children with severe viral encephalitis, 13 children with mild viral encephalitis and 12 normal children, who were treated in our hospital, were randomly selected. Before and after treatment, the concentrations of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, NF-κB level in serum and cerebrospinal fluid of children with viral encephalitis was positively related to the severity of the disease. [164].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NF-κB level in serum and cerebrospinal fluid of children with viral encephalitis was positively related to the severity of the disease. [164].…”
Section: Discussionmentioning
confidence: 99%
“…The full-text article could not be found in 21 studies (_((((xxx))))_)[ 80 , 104 – 123 ]. Based on the inclusion and exclusion criteria, 71 studies (_((((xxx))))_)[ 8 , 23 – 30 , 121 , 124 184 ] were considered for this study, of which 23 studies had sufficient quantitative data and were included in the meta-analysis and reported in this study (_((((xxx))))_)[ 25 , 28 – 30 , 125 127 , 131 , 134 , 140 142 , 144 , 147 , 149 , 152 , 156 , 175 , 178 – 180 , 183 , 184 ]. The remaining 48 studies were not included in the meta-analysis because they mostly reported qualitative data and did not contain sufficient quantitative data.…”
Section: Resultsmentioning
confidence: 99%